Physiological responses of tambaqui to therapeutic baths of mebendazole - Chagas, Edsandra Campos; Araújo, Lucelle Dantas de; Silva, André Luiz Ferreira da; Gomes, Levy de Carvalho; Brandão, Franmir Rodrigues (Pesquisa Agropecuaria Brasileira, 2006)
The objective of this work was to evaluate the physiological responses of tambaqui (Colossoma macropomum, Cuvier 1818) to therapeutic baths with mebendazole. Tambaqui juveniles (n = 108, mean weight 37.80±0.24 g) were submitted to therapeutic baths with mebendazole at 0, 100, 300 and 600 mg L-1, with three replicates, during 30, 60 and 120 minutes. No significant differences were observed for plasma ions (sodium, potassium and calcium) concentration and for hematological parameters (hematocrit, eritrocit numbers and corpuscular indices), except hemoglobin, which increase after exposure of 120 minutes in the mebendazole concentration of 300 mg L-1 was significant, similarly to the observed for glucose. Stress physiological indices evaluated showed that tambaqui maintains its homeostasis in concentrations until 600 mg L-1 of mebendazole for 120 minutes, presenting a good tolerance to mebendazole.